Brain vascular accident and contamination by Covid-19 (Research, Society and Development, 2022)
Cerebrovascular Accident (CVA) is defined as a neurological syndrome, which ranks second in terms of morbidity and mortality in the world. With the appearance of SARS-CoV-2, the new coronavirus, some scientific works present questions related to neurological complications. The present study aimed to verify the relationship between people diagnosed with COVID-19 and the appearance of a cerebrovascular accident (CVA), during the period of hospitalization in two medium-sized hospitals in the city of Vitória da Conquista - BA, at the beginning of December. January 2020 to February 2022. A quantitative and exploratory study was carried out, with a descriptive approach, based on the analysis of 100 medical records of patients diagnosed with COVID-19. For data collection, two instruments were developed, a sociodemographic questionnaire and a structured form to collect the data generated by SARS-CoV-2 and AVE. During the defined period, 12 medical records were analyzed. The results showed that SARS-CoV-2 infection can cause neurological sequelae, such as stroke.